Strukturwandel durch Fusionen im Ernaḧrungssektor: Ein anhaltender Konzentrationsprozess? - Gyde Neumann; Christoph Weiss (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– Structural change in the food industry by mergers and acquisitions: a persistent process of concentration? Mergers and acquisitions substantially affect the structure of the German food industry. This study analyses changes in the number of mergers and acquisitions for 21 German industries between 1976 and 1994. The results of an econometric panel data analysis show (a) a high degree of persistence, (b) distinct anti-cyclical fluctuations and a positive trend of merger activities as well as (c) significant effects of industry specific characteristics. Contrary to the available empirical literature the econometric model differentiates between industry characteristics of "acquiring" and "acquired" firms.
Keywords: 330; Ernährungsindustrie; Fusion; Unternehmenskonzentration; Deutschland